Life cycle assessment of H2-selective Pd membranes fabricated by electroless pore-plating. (20th September 2021) - Martinez-Diaz, D.; Leo, P.; Sanz, R.; Carrero, A.; Calles, J.A.; Alique, D.
Abstract: Pd-based membranes are attracting great attention to reach ultra-pure hydrogen in independent separators or combined with catalysts in membrane reactors. Many advances have been proposed for their fabrication over the last few years, reaching relatively thin Pd-films onto porous substrates with high permeation capacities and mechanical stability, although their commercialization and penetration in the industry are still scarce. At this point, it is important to complete all these technological advances with data about related economic and environmental implications during their fabrication to detect possible bottlenecks and select the best strategy. In this context, the current study presents for the first time a life cycle assessment focused on the preparation of Pd-based composite-membranes by Electroless Pore-Plating (ELP-PP). Two different types of composite membranes supported onto porous stainless steel tubes are analyzed, including or not an additional CeO2 intermediate layer between the support and the Pd-film. Precise experimental data of the fabrication process at laboratory-scale were considered to account for both materials and energy requirements. Thereafter, the environmental impacts were estimated through ReCiPe methodology by using the software Simapro 8.5. The results evidence that climate change (CC), human toxicity (HT), acidification (AC), freshwater ecotoxicity (FWE), metal depletion (MD) and fossil fuel resources depletion (FD) are the most relevant environmental impacts generated during the manufacturing of the Pd-based membrane. Under this perspective, palladium deposition appears as the manufacturing step with the highest impacts. It can be explained by the metal consumption and the high-energy consumption required for deposition cycles. Thus, the electricity mix of the country where the factory is located is critical to minimize the environmental impacts. For this reason, European countries are expected to be the most favorable ones for membrane fabrication. Finally, comparing both membrane types (with or without a CeO2 intermediate layer), it can be stated that the incorporation of the ceramic layer noticeably reduces the necessary amount of Pd to reach a fully dense membrane and therefore the associated environmental impacts. Highlights: Assessment of environmental impacts for diverse Electroless Pore-Plating membranes. Cleaning and drying steps are critical issues due to electricity consumption. CeO2 barriers improve membrane-performance and reduce environmental impacts in 35%. Energy requirements make the location of the membrane production center crucial.